E-learning and strategies for teaching Arabic language skills to non-native speakers - Yousef A. Baker, El-Ebiary; Ibrahim Babikir ELhag, Abd ELGadir; ELsaed Makki, ELbishr Ali Hassan (2020)
Teaching Arabic to non-native speakers receives great interest in our contemporary world, and this interest is derived from several sources; Including what is related to the status of the Arabic language from the Islamic faith, and the fact that its knowledge and insight in it needs that, and some of it is strategic that relates to the location of the Arab world from the map of the world, and some of it is political that relates to events in this region, and what prevails in it From the relations with all the countries of the world, including what is economic that relies on what God - the Almighty - has endowed with this region in terms of wealth and the energy potential that it occupies in directing the policies of countries, including what is culturally related to the morals of the Arab person And the characteristics inherited through generations. Therefore, efforts should be made to identify the easiest ways and means that help us spread this language and develop curricula that are appropriate and teach the Arabic language to speakers of other languages so that non-Arabs can learn the Arabic language in a short time and with less effort and a good level. And those interested in teaching foreign languages in general have reached a certain conviction, that the solution to educational problems lies in the availability of the means, methods, and methods of teaching from facilitating educational inputs that suit everyone in terms of their inclination, perception, and educational model, which prompted Educational institutions pay attention to education and communication technologies, and if the use of these means is necessary in relation to the various sciences, theoretical or applied, the importance is doubled in language teaching, and research will be limited to e-learning strategies and its role in teaching Arabic to non-native speakers.